2016
DOI: 10.1016/j.watres.2016.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Propidium monoazide RTqPCR assays for the assessment of hepatitis A inactivation and for a better estimation of the health risk of contaminated waters

Abstract: The waterborne transmission of hepatitis A virus (HAV), the main cause of acute hepatitis, is well documented. Recently, two ISO proposals for sensitive determination of this pathogen by RTqPCR in water and food have been published (ISO/TS 15216-1 and ISO/TS 15216-2), and could enable the formulation of regulatory standards for viruses in the near future. However, since detected viral genomes do not always correlate with virus infectivity, molecular approaches need to be optimized to better predict infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 19 publications
4
53
0
Order By: Relevance
“…Our results showed that we could not detect any infectious norovirus GI in seawater samples, possibly because of the low concentration of norovirus GI present in those samples. Similar results were reported in a previous study where 98% hepatitis A viruses present in river water were deemed non-infectious [33]. However, our results did indicate the low level of infectious norovirus GII present in one of the seawater samples.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that we could not detect any infectious norovirus GI in seawater samples, possibly because of the low concentration of norovirus GI present in those samples. Similar results were reported in a previous study where 98% hepatitis A viruses present in river water were deemed non-infectious [33]. However, our results did indicate the low level of infectious norovirus GII present in one of the seawater samples.…”
Section: Discussionsupporting
confidence: 92%
“…Because molecular methods are unable to discern between infectious and noninfectious particles, we predicted the infectivity of norovirus in the concentrated samples by treating the samples with the nucleic acid intercalating dye PMA propidium monoazide; (50 µmol/L) and Triton X surfactant (0.5%) before RT-qPCR; this enabled us to distinguish between virions with intact and altered capsids ( 9 ). Following this approach, estimated infectious levels in the 2 positive samples were 49 and 327 genome copies/L for norovirus GI and 33 and 660 genome copies/L for norovirus GII (Table).…”
Section: The Studymentioning
confidence: 99%
“…Photoactivatable intercalating dyes have begun to show promise in being able to selectively detect infectious HAV (Sanchez et al, 2012; Coudray-Meunier et al, 2015; Moreno et al, 2015; Fuster et al, 2016; Randazzo et al, 2018b) and human NoV (Parshionikar et al, 2010; Randazzo et al, 2016, 2018a; Jeong et al, 2017). Recently, Fraisse et al (2018) proposed PtCl 4 as a successful viability marker for human NoV.…”
Section: Resultsmentioning
confidence: 99%